2021
DOI: 10.1093/jn/nxab118
|View full text |Cite
|
Sign up to set email alerts
|

High Consumption of Ultra-Processed Food is Associated with Incident Dyslipidemia: A Prospective Study of Older Adults

Abstract: Background Ultra-processed food (UPF) consumption has been associated with higher cardiovascular disease (CVD) and mortality risks. Objectives The aim of this study was to assess the relationship between UPF consumption and incident dyslipidemia in older adults, where evidence is limited. Methods We studied a prospective cohort of 1082 community-dwelling adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 50 publications
2
33
0
Order By: Relevance
“…Other reasons are related to socio-economic inequalities, including lower education status of the mother or unemployed parents, which may lead to a preference for cheaper and less nutritious foods [105]. A different trend was observed for older subjects who showed a lower intake of UPF compared to younger subjects; the main UPF products included cookies and pastries, but also processed breads, breakfast cereals, and yogurts [16,128]. Compared to age, a minor variability was found for sex and/or BMI, which might differ for the net amount of UPF consumption but not for the percent of TEI from UPF.…”
Section: Discussionmentioning
confidence: 99%
“…Other reasons are related to socio-economic inequalities, including lower education status of the mother or unemployed parents, which may lead to a preference for cheaper and less nutritious foods [105]. A different trend was observed for older subjects who showed a lower intake of UPF compared to younger subjects; the main UPF products included cookies and pastries, but also processed breads, breakfast cereals, and yogurts [16,128]. Compared to age, a minor variability was found for sex and/or BMI, which might differ for the net amount of UPF consumption but not for the percent of TEI from UPF.…”
Section: Discussionmentioning
confidence: 99%
“…Donat-Vargas et al identified an increased risk of hypertriglyceridaemia (OR: 2.00 (1.04, 3.85)) and low-HDL cholesterol (OR: 2.04 (1.22, 3.41)), as well as a significant increase in blood triglycerides (β: 6.11 mg/dL (1.30, 10.91)) when comparing the highest vs. lowest tertile of UPF intake [ 136 ]. Adjustment for unprocessed or minimally processed food intake did not alter the increased risk of hypertriglyceridaemia (OR: 2.66 (1.20, 5.90)), low-HDL cholesterol (OR: 2.23 (1.22, 4.05)) or change in blood triglycerides (β: 6.87 mg/dL (1.48, 12.27)) [ 136 ].…”
Section: Review Of Prospective Studies Adjusting For Dietary Qualitymentioning
confidence: 99%
“…These adjustments are reported in Supplementary Table S2 . The significant associations between UPF intake and all-cause mortality, overweight or obesity, central obesity, T2DM, hypertension, gestational weight gain, neonatal anthropometrics and blood lipid profiles were unchanged following these dietary adjustments [ 103 , 108 , 113 , 114 , 120 , 123 , 135 , 136 ].…”
Section: Review Of Prospective Studies Adjusting For Dietary Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…As processed foodstuffs (Table 2) and drinks contain high phosphate concentrations, CKD patients should cut their consumption of these food products [212,213]. Multiple studies reported that high levels of phosphate preservatives are found in convenience food or ready-to-eat meal [77,[214][215][216][217][218][219][220][221][222][223][224][225][226][227][228][229]. Additionally, high serum phosphorus is incorporated with the cardiac death toll in long-lasting kidney diseases [78,[230][231][232].…”
Section: Phosphate Toxicity Affecting Renal Physiologymentioning
confidence: 99%